Pengembangan dan Pemberdayaan Masyarakat Pemilik Usaha Melalui Dinas Perdagangan dan Perindustrian Kulonprogo - Daery Farras Saputro; Andriyastuti Suratman (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
The existence of infrastructure and development that continues to develop in Kulon Progo, such as the YIA Airport in Kulon Progo, hotels and shopping centers can lead to rapid development growth in Kulon Progo. With development increasing rapidly but not accompanied by the development of human resources in the surrounding area, this has resulted in the marginalization of the surrounding community. The author's aim is to analyze the activities carried out by the Kulon Progo government to increase the capacity of the Kulon Progo community. Can also analyze problems that arise in the development process and how the Department handles them. A qualitative approach was chosen for this research process, namely descriptive research. The data sources used are primary data obtained during the research process and secondary data from books and other literature. The data collection process was carried out by interviews, direct observation and documentation. The research results include plans for development and empowerment activities prepared by the department taking into account various agency linkages and the needs of business actors in Kulon Progo. The Department carries out various programs such as training to increase production capacity, improving central management, issuing permits to increase business capacity in Kulon Progo. Monitoring and evaluation of activities is also carried out to determine the obstacles and successes of activity programs.